What caused the recent "Warm Arctic, Cold Continents" trend pattern in winter temperatures?. Issue 10 (25th May 2016) - Sun, Lantao; Perlwitz, Judith; Hoerling, Martin
Abstract: The emergence of rapid Arctic warming in recent decades has coincided with unusually cold winters over Northern Hemisphere continents. It has been speculated that this "Warm Arctic, Cold Continents" trend pattern is due to sea ice loss. Here we use multiple models to examine whether such a pattern is indeed forced by sea ice loss specifically and by anthropogenic forcing in general. While we show much of Arctic amplification in surface warming to result from sea ice loss, we find that neither sea ice loss nor anthropogenic forcing overall yield trends toward colder continental temperatures. An alternate explanation of the cooling is that it represents a strong articulation of internal atmospheric variability, evidence for which is derived from model data, and physical considerations. Sea ice loss impact on weather variability over the high‐latitude continents is found, however, to be characterized by reduced daily temperature variability and fewer cold extremes. Key Points: Arctic sea ice loss is responsible for "Warm Arctic" but not for "Cold Continents" Recent "Cold Continents" are an extreme event of natural decadal variability Sea ice loss reduces temperature variability and risk of cold extremes in high‐latitude continents